Quality MP-ASI Education Sourced From Local Basic Ingredients In Desa Lam Isek, Peukan Bada District Aceh Besar District - Martina Tina; Yuli Zuhkrina Yuli; Kiki Kiki Rezeki Amelia (CV SWA Anugerah, 2023)
Providing appropriate complementary foods when children are 6 months and older plays an important role in fulfilling children's nutritional intake. Malnutrition at the beginning of life will have an impact on the quality of human resources (HR) in the future. Children will experience growth failure. Nutrition problems for toddlers in Indonesia based on the 2018 Riskesdas are still very high, such as the prevalence of stunting in toddlers is 30.8%, the prevalence of very poor and very thin toddlers is 10.2% and obese toddlers are 8%. The nutritional status of toddlers can be caused by maternal knowledge, parenting patterns, food intake, exclusive breastfeeding and infectious diseases. One effort that can be made to support the provision of optimal nutritional intake is by increasing the knowledge and skills of mothers of toddlers in processing MPASI using local and diverse food ingredients in a good, practical and safe manner through education. The methods used in this education are lectures and questions and answers, and pretests and posttests are also carried out. As a result of the outreach and outreach, there was an increase in the number of mothers who had good knowledge about quality MP-ASI, namely from 17.31% to 75%. It is hoped that health workers can provide education about providing quality MP-ASI by utilizing local food sources and increasing material about nutrition as well as motivating mothers to maintain good and correct parenting patterns.